2009
DOI: 10.1111/j.1526-4637.2008.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physician and Patient Gender on Pain Management in the Emergency Department—A Multicenter Study

Abstract: Provider gender as opposed to patient gender appears to influence pain management decisions in the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
92
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 41 publications
6
92
7
Order By: Relevance
“…Bell & Hudson, 2001;Criste, 2003;Turk & Okifuji, 1999;van Lennep et al, 1999), and still a few others have shown biases against men (e.g. Bergelson & Tommaso, 1995;Blum, Slade, Boden, Cabin, & Caulin-Glaser, 2004;Safdar et al, 2006). In a nutshell, the pattern of results seems inconclusive.…”
Section: Introductionmentioning
confidence: 62%
“…Bell & Hudson, 2001;Criste, 2003;Turk & Okifuji, 1999;van Lennep et al, 1999), and still a few others have shown biases against men (e.g. Bergelson & Tommaso, 1995;Blum, Slade, Boden, Cabin, & Caulin-Glaser, 2004;Safdar et al, 2006). In a nutshell, the pattern of results seems inconclusive.…”
Section: Introductionmentioning
confidence: 62%
“…This pattern emerges both in vignettes studies depicting chronic low-back pain patients (CLBP) 53,54 and in a prospective observational study of physicians' PMP in the ER. 48 . Therefore, like for primary-care preventive practices 10,12,21,49 , patient sex seems to have a different impact on male and female physicians' PMP.…”
Section: Introductionmentioning
confidence: 99%
“…They were influenced by either the gender or race of their patients [29]. Safdar et al reported that the gender of ED physicians influenced the quantity of opioid analgesics they prescribed to those of their same gender [23].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies look at the effect of patient characteristics on the decision of the medical provider to prescribe pain medications [4,[15][16][17][18][19][20][21][22], but few describe the variability of prescribing habits of ED providers [23][24][25]. The objective of our study was to describe the opioid prescribing practices of physicians and PAs, to include civilian and military providers, in an emergency department when treating patients with a discharge diagnosis of chronic pain.…”
Section: Introductionmentioning
confidence: 99%